Pengaruh Web Series Keluarga Hijrah di Youtube terhadap Akhlak Siswa MTS Darul Ulum Lamongan - Aura Safira El Acida; Rasiin, Rasiin; Dimyati Sajari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Web Series are short films broadcast on the internet and are divided into several episodes. With the existence of a web series, it makes moral development easier and more attractive to students. This hijrah family not only build morals when at home, but also in the school environment. This study uses a quantitative method with a type of regression. Data collected using documentation and questionnaires, in which researchers went directly to the field to collect data. The results of this study show that there is a significant influence between the variables of the Hijrah Family Web Series on Youtube on the morals of students. Thus, this research is in line with the research of Intan Aji Pangestu et al, Nur Isnainy Hidayati et al, and Nasran Azizan et al.